Governance matters Relationship model of Governance, Leadership and management - Stahlke Les; Kaufmann, Daniel, 1951-; Kraay, Aart.; Mastruzzi, Massimo
The Worldwide Governance Indicators (WGI) project reports aggregate and individual governance indicators for 212 countries and territories over the period 1996-006, for six dimensions of governance: Voice and Accountability Political Stability and Absence of Violence Government Effectiveness Regulatory Quality Rule of Law Control of Corruption The aggregate indicators combine the views of a large number of enterprise, citizen and expert survey respondents in industrial and developing countries. The individual data sources underlying the aggregate indicators are drawn from a diverse variety of survey institutes, think tanks, non-governmental organizations, and international organizations. The six aggregate indicators and the underlying data sources can be viewed interactively on the Indicators page of this website. Documentation of the latest update of the WGI can be found in "Governance Matters VI: Governance Indicators for 1996-006." Further documentation and research using the WGI is available on the Resources page of this website.
Viewed on (July 12, 2007).
"The WGI are produced by: Daniel Kaufmann, World Bank Institute, Aart Kraay, World Bank Development Economics Research Group, Massimo Mastruzzi, World Bank Instititute.
Each year this Web site is updated overall and given a range of dates, for example, 1997-2007 for date 2008.
Keywords: Politics, Practical; Political stability; Rule of law